2015
DOI: 10.1021/acs.inorgchem.5b01472
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Synthesis, Crystal Structures, and Properties of CdMn7O12 and SrMn7O12 Perovskites

Abstract: We synthesize CdMn7O12 and SrMn7-xFexO12 (x = 0, 0.08, and 0.5) perovskites under high pressure (6 GPa) and high temperature (1373-1573 K) conditions and investigate their structural, magnetic, dielectric, and ferroelectric properties. CdMn7O12 and SrMn7O12 are isostructural with CaMn7O12: space group R3̅ (No. 148), Z = 3, and lattice parameters a = 10.45508(2) Å and c = 6.33131(1) Å for CdMn7O12 and a = 10.49807(1) Å and c = 6.37985(1) Å for SrMn7O12 at 295 K. There is a structural phase transition at 493 K i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 48 publications
9
61
1
Order By: Relevance
“…19 Using the present results, we showed that they also have low-temperature structural modulations. This behaviour is difficult to rationalize qualitatively.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…19 Using the present results, we showed that they also have low-temperature structural modulations. This behaviour is difficult to rationalize qualitatively.…”
Section: Discussionsupporting
confidence: 64%
“…The observed DSC anomalies are intrinsic as confirmed by low-temperature synchrotron XRPD results given below. A baseline of the DSC curves can be more or less unambiguously determined in PbMn 7 O 12 , and the estimated enthalpy of the transition is about 0.16 J/g; this value is about 40 times smaller that the enthalpy of the R-3-to-Im-3 transition (6.6 J/g) 19. Iron doping had noticeable effects on the DSC anomalies at T CO and T OO reducing the phase transition temperatures and significantly broadening the DSC effects.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…It could be due to extrinsic factors such as space trapped charges at grain boundaries. We note that a broad and high pyroelectric peak was often reported in the quadruple perovskite manganites such as CaMn 7 O 12 , and its origin is quite controversial 27,3444 .
Fig. 5Spin-induced ferroelectricity in the binary perovskite Mn 2 O 3 .
…”
Section: Resultsmentioning
confidence: 85%